Microplastics/microfibers in settled indoor house dust—exploratory case study for 10 residential houses in the Kanto area of Japan - Eunsu Lim; Hirofumi Tanaka; Yuan Ni; Yifan Bai; Kazuhide Ito (Japan Architectural Review, 2022)
Abstract Although microplastic (size ≤5 mm) pollution in marine ecosystems has received global attention, the presence of microplastics and microfibers in indoor environments is also a major concern. Compared to the available field survey data on microplastics in the ocean, such information remains limited for indoor environments. Microplastics in indoor environments may act as adsorbents for chemical compounds, which may result in multiple adverse health effects on residents. Establishment of reproducible sampling and analysis methods aiding comprehensive field measurements of indoor microplastics in Japan is required. This study conducted the first field survey of indoor microplastics in settled dust in 10 residential houses in the Kanto area of Japan and explored their composition and morphology. Micro‐Fourier transform infrared (μ‐FT‐IR) spectrophotometry and laser direct infrared (LDIR) analysis were used for the qualitative analysis of microplastics. The μ‐FT‐IR and LDIR analyses revealed the presence of large quantities of microplastics in the settled dust. The samples were composed of cellulose, polyethylene terephthalate, polyethylene, alkyd resins, polysulfone, polyvinyl alcohol, and polyamides. The μ‐FT‐IR and LDIR analyses were suitable for identifying large fibrous materials and small particles, respectively. Thus, the two methods are complementary for the comprehensive identification of microplastic composition in settled dust.